Weakness of civil society in Ukraine: A mechanism-based - Kseniia Gatskova; Maxim Gatskov (Institut für Ost- und Südosteuropaforschung (IOS), 2012)
This study explores the determinants of the low level of civic engagement in Ukraine. Applying the methodological framework of analytical sociology we consider different social mechanisms that explain the weakness of Ukrainian civil society. First, we discuss how the political system and economic performance of the country shape beliefs, values and motives of people by creating the context for their actions. Second, we focus on different aspects of people's experience during the Soviet times to rule out a number of hypotheses concerning unwillingness of citizens to join formal voluntary organizations. Using the results of the individual-level data analysis we show that the specific features of the Homo Sovieticus -socio-cultural type- such as passivity towards management of the own life, absence of political identification, and reliance on informal networks affect negatively the propensity of people to be members of civic organizations. These effects are complemented by the negative impact of post-Soviet transformation disappointment and subjective perception of low social status. Based on the results of analyses we formulate suggestions concerning possible ways to foster the civil society development in Ukraine.
urn:nbn:de:101:1-20121001755
Keywords: 330; Gesellschaft; Ukraine